If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = 50 Reorder the terms: 7 + 5x = 50 Solving 7 + 5x = 50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 5x = 50 + -7 Combine like terms: 7 + -7 = 0 0 + 5x = 50 + -7 5x = 50 + -7 Combine like terms: 50 + -7 = 43 5x = 43 Divide each side by '5'. x = 8.6 Simplifying x = 8.6
| -x-14=1 | | 3y+8y-19=17+5y | | 10/60=x/100 | | 12-2(4x-5)=-2 | | 35=6v-5+4v | | 6(2x-1)+2(x+11)=2 | | X/x^4/24 | | (5x/2)-9=(2x-7/6) | | 0=3(2x+4) | | y=-3.5x-4.5 | | 6u-4u=10 | | 198=5x+3(-7x+2) | | (m=5)/5=3 | | 3x+25+-37=126 | | 44=2v | | -8x+5(2x-1)=4x+7 | | -4p+2+20p=15p+18 | | 7/m=3/9 | | 5+2(x+3)=11 | | y=-3.5-4.5 | | 3x-5(-x-17)=181 | | 198=5x+3(-7+2) | | 36/x=30/42 | | n/125=4/100 | | (4x)(-3xy^2)=-12x^2y^2 | | 45t+9= | | x=16+-0.4y | | 4c+19c+19=-20+20c | | 7x-2=5x-3+2x+1 | | c=1/2e*m | | .25x+.10y=4 | | 686=7(-8x-22) |